Making Genes Green: Creating Green Fluorescent Protein (GFP) Fusions with Blunt-End PCR Products. (July 1998) - Lo, Wayne; Rodgers, William; Hughes, Thomas
The jellyfish green fluorescent protein (GFP) has proven to be a useful tool in protein localization and trafficking studies. Fused to GFP, a protein of interest can be visualized and tracked in vivo through fluorescence microscopy. However, the process of making these fusion proteins is often tedious and painstaking. Here, we describe a simple and quick method for creating GFP fusion proteins using blunt-end PCR product ligation.